Greying Malaysians: strategies for promoting and supporting healthy and productive ageing - Phua, Kai Lit (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2007)
Population ageing is inevitable in Malaysia as a result of declining fertility rates. Steps can be taken to face this challenge. These include ways to promote “healthy ageing” and “compression of morbidity” and ways to promote “productive ageing”, i.e., keeping the elderly economically and socially engaged. This article, based on a review of the literature, argues that it is illogical to force people into compulsory retirement at an arbitrary age when they can continue to contribute actively to society. Instead, ways can be devised to promote healthy ageing, prolonging independence and encouraging productive ageing through gradual economic and social disengagement of the individual depending on the individual’s physical health, mental health, contribution to society and personal inclination and preferences. Public policy in general and public health policy in particular can be designed or redesigned to help achieve this.